2017
DOI: 10.20319/pijss.2017.31.80100
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Innovative Potential on Small Business Performance

Abstract: The aim of the paper is to describe and identify the level of innovative potential of micro, small and medium-sized enterprises (SMEs) and to assess its impact on small business performance.Three research questions were formulated. The author's empirical research in the form of a survey conducted on a sample of 1,741 SMEs in the European Union Member States served the aim of the paper. The measurements were based on an original synthetic index of small business innovative potential (6 items, alpha Cr. = 0.841)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The greater the number of employees and the higher the level of human capital, the higher the levels of product, process and organizational innovation. These findings may be explained by the fact that in many small businesses employing a small number of employees, the manager who in most cases is the business owner is very dominant and does not usually involve other employees in making marketing decisions (Cardoni et al , 2018; Matejun, 2017; Yew and Aspinwall, 2004), which are more related to management aspects and require less technical knowledge. In addition, employees with engineering or science education are less expected to be involved in areas of marketing innovation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater the number of employees and the higher the level of human capital, the higher the levels of product, process and organizational innovation. These findings may be explained by the fact that in many small businesses employing a small number of employees, the manager who in most cases is the business owner is very dominant and does not usually involve other employees in making marketing decisions (Cardoni et al , 2018; Matejun, 2017; Yew and Aspinwall, 2004), which are more related to management aspects and require less technical knowledge. In addition, employees with engineering or science education are less expected to be involved in areas of marketing innovation.…”
Section: Discussionmentioning
confidence: 99%
“…‏Small businesses usually have a single owner or a small group of shareholders managed by the primary owner. Moreover, these businesses are characterized by autonomy as they are not part of a corporate group, and thus the owner has unrestricted authority and effective control over all business activity (Carland et al , 2007; Schollhammer and Kuriloff, 1997; Matejun, 2017). Nonetheless, the most important distinguishing characteristic of small businesses is their unique management style.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found that customers' orientation affects incremental services while inter-functional orientation affects radical service innovation and that both increase firm performances. The work of Matejun (2017) entitled the effect of innovation potential on small business performance had the objective to describe the level of innovation potential of the SME and assessed its impact on performance. The study surveyed 1741 SMEs in the European Union Member State.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Small businesses are defined as businesses that employ up to 50 employees (European Commission 2003; Prime Minister's Office 2014). They are often characterized by limited regional activity, relatively small market share, operate in niche and highly specific markets and typically have a single or small group of owners, managed by the primary owner (Carland et al 2007;Schollhammer and Kuriloff 1997;Matejun 2017). In the manufacturing sector particularly, many small businesses act as specialist suppliers of parts, components and subassemblies, and as subcontractors to large companies (Yew Wong and Aspinwall 2004).…”
Section: Small Businessesmentioning
confidence: 99%